Student Political Participation and the Future of Democracy in Indonesia - Zainul Djumadin (AL-ISHLAH: Jurnal Pendidikan, 2021)
Political participation means we will talk about the activities or activities of people as citizens in political life. Every citizen is required to participate in the process of making and formulating all state political policies. Students are intelligent individuals who are significant assets for a country. Students' political participation will feel more meaningful because they are considered and know that they are also idealistic and have not been contaminated by various destructive ideas. Therefore, this study aims to determine student political participation and the future of democracy in Indonesia. This study uses a qualitative approach with descriptive methods in analyzing research data. Political participation of students in democracy can be seen by their participation in democratic elections as novice voters, with the participation of students in elections will provide political sensitivity and stimulation to students to be more actively involved in politics, with them being more actively involved in politics will be able to develop social character so that they have independence in determining their desires and are not easily influenced by persuasion and invitations from certain parties. In this study, there is also a need for political education for students. It is not easy to swallow false information that specific individuals do not truly create due to the lack of experience and knowledge in the field of politics in Indonesia.